2015
DOI: 10.3390/w7084496
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluation of a Stormwater Treatment Train with Pit Baskets and Filter Media Cartridges in Southeast Queensland

Abstract: Field monitoring of a stormwater treatment train has been underway between November 2013 and May 2015 at a townhouse development located at Ormiston, southeast Queensland. The research was undertaken to evaluate the effectiveness of a 200 micron mesh pit basket in a 900 square format and an 850 mm high media filtration cartridge system for removing total suspended solids and nutrients from stormwater runoff. The monitoring protocol was developed with Queensland University of Technology (QUT), reflecting the Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 3 publications
(1 reference statement)
3
10
0
Order By: Relevance
“…Influent concentrations for TSS and TN at the study site (Table 6) were significantly lower (TSS p < 0.001, TN p < 0.001) than the typical values for Australian commercial catchments reported by Duncan [23] and those recommended by industry for use in Australian pollution modelling studies and used within the software tool, Model for Urban Stromwater Improvement (MUSIC) [24]. Similarly affected PSTD performance results have been observed by the authors from other field evaluation sites [25]. Results from these other studies have been shown to differ by up to 30% for TN and 20% for TP, where low influent concentrations result in 0% or negative CRE.…”
Section: Resultssupporting
confidence: 55%
“…Influent concentrations for TSS and TN at the study site (Table 6) were significantly lower (TSS p < 0.001, TN p < 0.001) than the typical values for Australian commercial catchments reported by Duncan [23] and those recommended by industry for use in Australian pollution modelling studies and used within the software tool, Model for Urban Stromwater Improvement (MUSIC) [24]. Similarly affected PSTD performance results have been observed by the authors from other field evaluation sites [25]. Results from these other studies have been shown to differ by up to 30% for TN and 20% for TP, where low influent concentrations result in 0% or negative CRE.…”
Section: Resultssupporting
confidence: 55%
“…Although specific treatment technologies can reduce specific contaminants, oftentimes synergistic gains can be realized via pairing two or more types of treatment systems in series or in other combinations (i.e., treatment train approach such as filtration and sanitation). This coupling is often most effective when targeting different types of physical, chemical, and biological contaminants (e.g., agrichemicals and pathogens, or pathogens and sediment), since there is no single treatment system that will effectively manage all types of contaminants [32][33][34][35][36].…”
Section: Effective Measures For Remediation Of Recycled Watermentioning
confidence: 99%
“…Although each of the treatment technologies discussed above can help reduce environmental impacts associated with production runoff, additional gains in treatment efficacy can be realized via pairing two or more types of treatment systems in series or other combinations which are synonymous with treatment train or chain. This coupling is often most effective when targeting different types of physical, chemical, and biological contaminants (e.g., agrichemicals and pathogens, or pathogens and sediment), since there is no single treatment system that will effectively manage all types of contaminants (Biswas et al 2007 ; Drapper and Hornbuckle 2015 ; Gearheart 1999 ; Kabashima et al 2004 ; Nyberg et al 2014 ). Much of the research with treatment trains has been focused on stormwater runoff (Campbell et al 2004 ) and wastewater treatment systems (Zeng et al 2016 ), with fewer studies focused on agricultural water treatment trains for container-grown crop production.…”
Section: Remediation Technologiesmentioning
confidence: 99%